PROGNOSTIC PARAMETERS OF HYDRODYNAMIC TECHNICAL AND TACTICAL TRAINING OF PARALYMPIC SWIMMERS IN THE SPORT OF THE BLIND - Vinokurov, L.V.; Mosunov, D.F.; Tveryakov, I.L. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analytical and empirical identification of predictors of special technical and tactical training of highly qualified athletes in Paralympic swimming for the blind. Methods and structure of the study. The study included a qualitative analysis of materials previously obtained by surface and underwater photo and video recording of the phases of the swimming cycle when Paralympians swim in various styles, sometimes with the use of LED indicators; an expert survey and a thematic analysis of the experience of the leading coaches of highly qualified (Master of Sports of Russia, International Master of Sports of Russia, Honored Master of Sports of Russia) swimmers of the blind sport was carried out. Results and conclusions. It is shown that Paralympic swimmers are characterized by two groups of predictors - specific and typical, reflecting what needs to be eliminated or compensated for by the coach and athlete in swimming technique. It is argued that deviation predictors are not technical errors in swimmers with visual impairments, but characterize an initially different organization of locomotion. The substantive differences of the predictors and the possibility of their correction in the selection of adequate methods have been established and described.